Management of direct foreign investments as an element of the socioeconomic development of countries - Taraniuk, Leonid; Korsakiene, Renata; Taraniuk, Karina; Dyakova, Nataliya; Shabelnyk, Karina (Національний технічний університет "Харківський політехнічний інститут", 2023)
The article analyses the main modern trends in the management of direct foreign investments as an element of the socio-economic development of the countries of the world. The theoretical provisions of the organizational and economic support of direct investments in the socio-economic development of countries, which make it possible to form a theoretical basis and concepts of economic growth based on the paradigm of sustainable socio-economic development, have been analysed. Methodological support for the management of direct foreign investments of countries has been improved, which includes a graph-analytical analysis of direct foreign investments of countries with the aim of implementing regulatory mechanisms on the part of states to improve the efficiency of this management. The main organizational approaches to the positive impact of investment demand at the state level have been studied, which makes it possible to form effective organizational support for direct investments by state bodies and investors. The dynamics of investment flows of countries in the conditions of globalization, which makes it possible to form a vision of effective organizational and economic mechanisms of direct foreign investments of countries, is considered. Global trends in ensuring and developing the investment climate were noted in order to establish the main directions of increasing the level of investment attractiveness of countries. The regional section of the problems and prospects of investment development of Ukraine was studied, which makes it possible to form a strategic vision of the socio-economic development of the country from the position of attracting foreign investors in the field of formation of economic and social factors of attracting foreign capital in the tap and formation of an attractive investment climate in the country as a whole. A conclusion was made regarding the need to implement the organizational and economic support of direct foreign investment in the socio-economic development of the countries of the world, which includes state policies, strategies and tactical tools, the formation of proposals and recommendations regarding the regional aspects of the management of direct foreign investment in the country in the conditions of its post-war social economic development.

У статті проаналізовано основні сучасні тренди управління прямими іноземними інвестиціями як елементу соціально-економічного розвитку країн світу. Проаналізовано теоретичні положення організаційно-економічного забезпечення прямих інвестицій в соціально-економічному розвитку країн, які дають змогу сформувати теоретичний базис та концепції економічного зростання, базуючись на парадигмі сталого соцільно- економічного розвитку. Удосконалено методичне забезпечення управління прямими іноземними інвестиціями країн, яке містить графоаналітичний аналіз прямих іноземних інвестицій країн з метою впровадження регуляторних механізмів з боку держав щодо підвищення ефективності даного управління. Досліджено основні організаційні підходи щодо позитивного впливу інвестиційного попиту на державному рівні, що дає змогу сформувати дієве організаційне забезпечення прямих інвестицій з боку державних органів та інвесторів. Розглянуто динаміку інвестиційних потоків країн в умовах глобалізації, яка дає змогу сформувати бачення ефективних організаційно-економічних механізмів прямих іноземних інвестицій країн. Відзначено світові тенденції забезпечення та розвитку інвестиційного клімату з метою встановлення основних напрямів підвищення рівня інвестиційної привабливості країн. Досліджено регіональний розріз проблем та перспектив інвестиційного розвитку України, що дає змогу сформувати стратегічне бачення соціально-економічного розвитку країни з позиції залучення іноземного інвестора у сфері формування економічно-соціальних чинників залучення іноземного капіталу в крані та формування привабливого інвестиційного клімату в країні в цілому. Зроблено висновок, щодо необхідності реалізації організаційно-економічного забезпечення прямих іноземних інвестицій у соціально-економічного розвитку країн світу, яке містить державні політики, стратегії та тактичні інструменти, формування пропозицій та рекомендацій щодо регіональних аспектів управління прямими іноземними інвестиціями в країні в умовах повоєнного її соціально-економічного розвитку.
Управління прямими іноземними інвестиціями як елемент соціально - економічного розвитку країн
Keywords: countries; management; approach; indicator; країни; управління; підхід; індикатор